Mixed-metal d-f phosphonate frameworks: photoluminescence and magnetic properties - Rocha, Joao (2011)
The synthesis and structural characterisation of a novel family of highly symmetric (rhombohedral crystal system) frameworks, incorporating d- and f-block elements formulated as [LnFeIIIFeII 6(Hpmida)6]·nH2O [Ln = Nd3+ (1), Gd3+ (2), Tb3+ (3), Er3+ (4)] is reported. This is the second example of a family of porous mixed d-f MOFs containing high-spin Fe2+ centres. These materials were prepared from an eutectic mixture (1:1 molar ratio, choline chloride/malonic acid) with a small amount of added water and isolated directly in large amounts as single crystalline phases. The structural details were revealed by single-crystal X-ray diffraction, variable-temperature powder X-ray diffraction, thermogravimetry, vibrational and Mössbauer spectroscopy and electron microscopy (SEM and EDS). Networks are assembled by unusual [Fe2(Hpmida)2]2– dimeric units, which connect to each other and to the lanthanide centres to form a 3D porous framework. The empty voids of this framework accommodate chargebalancing Fe3+ cations and uncoordinated water molecules, which are readily released without structural collapse at temperatures below 250 °C. The photoluminescence and magnetic properties of the compounds were studied at ambient and low temperature.